Empowering stem culture among the younger generations through junior data science program / Nooradilla Abu Hasan ... [et al.] - Abu Hasan, Nooradilla (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Junior Data Science Program Science, Technology, Engineering and Mathematics (STEM) has become an essential field of study at the tertiary level towards producing experts among Malaysians (Idris, Govindasamy, & Nachiappan, 2023). At a very young age, many programs related to STEM have been developed and run by many agencies either government or private sectors in order to prepare and fulfil the requirements. Robotic Program is one of the active programs towards STEM encouragement among the school's children (Yahaya & Lajium, 2017) College of Computing, Informatics, and Mathematics (KPPIM), UiTM Negeri Sembilan Branch, Seremban Campus has organised the Junior Data Science Program on May 2023. This program is the second series since it was introduced in 2022 and is an ongoing program to generate income for the KPPIM. Junior Data Science Program focuses on empowering STEM education and skills for kids starting 6 years and above and been conducting during schools' holidays. Furthermore, this program was divided into 2 parts. The first is Robotics for Beginners on May 30, and the second is Robotics on May 31, 2023.